The Strategic CFO Creating Value in a Dynamic Market Environment - Hommel, Ulrich; Fabich, Michael; Schellenberg, Ervin; Firnkorn, Lutz.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
The role of the Chief Financial Officer (CFO) has substantially changed in a world characterized by globalized financial markets and truly global products. The accelerated development of new technologies, products, and markets has led to an increasingly dynamic and uncertain competitive situation. The book demonstrates and discusses the impact of this changing corporate environment on the role and responsibilities of the CFO. A more holistic view that integrates business and financial decisions is required in order to manage these challenges of globalization. The book shows how the CFO can adopt and implement this management approach and thus play a vital role in the firm$1 (Bs value creation.s
Strategy-Linked Approaches to Risk Management and Corporate Financing -- Coping and Benefiting from the Dynamics of Financial Markets -- Linking the Dynamics of Financial Markets and Product Markets.
Keywords: Economics; Industrial management; Economics/Management Science; Finance/Investment/Banking.; Management/Business for Professionals